IMMUNOSTIMULANT EFFECTS OF PROPOLIS: A study of cytokine production - Mutiara Sani Demira Putri; Hannie Fitriani; Yandi Syukri; Arba Pramundita Ramadani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Propolis is a natural substance derived from bee resin and has long been used in traditional medicine because of its diverse bioactive compounds, especially flavonoids. This study aims to assess the immunostimulant effects of propolis on cytokine expression based on existing scientific research. A narrative review was conducted by collecting literature from PubMed, ScienceDirect, and Google Scholar. Initially, 48 articles were identified, and 15 articles that met the inclusion criteria were further analyzed. The results show that propolis has immunomodulatory activity through multiple mechanisms, including inhibiting the NF-κB pathway, reducing COX-2 expression, and suppressing nitric oxide (NO) production. Propolis also boosts macrophage activation, promotes phagocytosis, and increases the expression of pro-inflammatory cytokines such as IL-1β, IL-6, IL-2, and IFN-γ. However, under excessive inflammatory conditions, propolis decreases pro-inflammatory cytokine expression, indicating an adaptive immunoregulatory response. In conclusion, propolis has strong potential as a natural immunostimulant that works contextually according to the host’s immunological status and may be developed as a future herbal therapeutic agent.